Oral vitamin B12 can change our practice. Issue 930 (1st April 2003) - Nyholm, E; Turpin, P; Swain, D; Cunningham, B; Daly, S; Nightingale, P; Fegan, C
Abstract : Oral vitamin B12 can provide an effective alternative to intramuscular injections, so giving patients a choice and reducing costs in primary care. This study investigated the effectiveness, safety, and acceptability of oral vitamin B12 as replacement therapy in patients with vitamin B12 deficiency in a city general practice population. Forty patients previously maintained on vitamin B12 injections were given 1000 μg of oral cyanocobalamin daily for up to 18 months. All the patients maintained satisfactory serum B12 levels and showed normal haematology and neurology. Compliance and acceptability was excellent. The time for a change in practice has indeed arrived.